Development of exigencial diagnosis methodology applied to building rehabilitation - João Carlos Gonçalves Lanzinha (2002)
In the European context the rehabilitation of buildings will continue to grow during next years, consolidating as a great importance sector in the construction dominion. According to this scenery, it is important to develop a new methodology of exigencial inspection permitting that all the intervening in the process of building rehabilitation dispose of a work instrument to obtain a quickly, correct and appropriate information on the building intervention. In this article it is described the development of a new diagnosis methodology based on the exigencial evaluation of the constructive elements, with special incidence in the building envelope.